2018
DOI: 10.1126/science.aan2261
|View full text |Cite
|
Sign up to set email alerts
|

Paternally inherited cis-regulatory structural variants are associated with autism

Abstract: The genetic basis of autism spectrum disorder (ASD) is known to consist of contributions from de novo mutations in variant-intolerant genes. We hypothesize that rare inherited structural variants in cis-regulatory elements (CRE-SVs) of these genes also contribute to ASD. We investigated this by assessing the evidence for natural selection and transmission distortion of CRE-SVs in whole genomes of 9274 subjects from 2600 families affected by ASD. In a discovery cohort of 829 families, structural variants were d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
172
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(181 citation statements)
references
References 33 publications
8
172
0
1
Order By: Relevance
“…62 Indeed, early efforts to deploy WGS in cardiovascular disease, autism, and type 2 diabetes were largely consistent in their analyses of SNVs using GATK, but all studies have differed in their analyses of SVs. 25,37,50,[57][58][59]63,64 Thus, while ExAC and gno-mAD have catalyzed remarkable advances in medical and population genetics, the same opportunities for new discovery and translational impact have not yet been realized for SVs. Although gnomAD-SV is by no means comprehensive, the nearly half-million SVs it contains were derived from WGS methods and a reference genome that match those currently used in many research and clinical settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…62 Indeed, early efforts to deploy WGS in cardiovascular disease, autism, and type 2 diabetes were largely consistent in their analyses of SNVs using GATK, but all studies have differed in their analyses of SVs. 25,37,50,[57][58][59]63,64 Thus, while ExAC and gno-mAD have catalyzed remarkable advances in medical and population genetics, the same opportunities for new discovery and translational impact have not yet been realized for SVs. Although gnomAD-SV is by no means comprehensive, the nearly half-million SVs it contains were derived from WGS methods and a reference genome that match those currently used in many research and clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…These scores have become core resources in human genetics. [21][22][23] Existing metrics like pLI are reliant on SNVs, and while previous studies have attempted to compute similar scores using large CNVs detected by microarray or to correlate deletions with pLI, 37,38 no gene-level metrics comparable to pLI exist for SVs at WGS resolution. To gain insight into this problem, we estimated the number of rare SVs expected per gene while adjusting for gene length, exon-intron structure, and genomic context.…”
Section: Relevance To Disease Association and Clinical Geneticsmentioning
confidence: 99%
“…The homozygous FEZF2 allele may possibly impact on cis elements involving deregulation of the FEZF2 gene. Such cis-regulatory structural variants associated with autism have been recently described (53). FEZF2 is also part of a developing human brain gene co-expression network enriched for neurodevelopmental disorder risk genes that includes ASD high-risk genes such as TBR1, CTTNBP2, and DSCAM (44).…”
Section: Discussionmentioning
confidence: 98%
“…Besides the above‐described studies analyzing WGS data with an emphasis on de novo SNV and short indels, another large‐scale WGS study primarily focusing on structural variants (SV; e.g., large deletion, insertion, inversion, and mobile element insertions) was recently reported . In this study, the authors first selected SV categories that showed depletion in the real data when compared with a simulated dataset generated by randomly distributing SV in the genome.…”
Section: Rapidly Expanding Knowledge On Functional Non‐coding Elementsmentioning
confidence: 99%